Association between serum vitamin D and uric acid in the eastern Chinese population: a population-based cross-sectional study - Chen, Yingchao; Cheng, Jing; Chen, Yi; Wang, Ningjian; Xia, Fangzhen; Chen, Chi; Han, Bing; Lu, Yingli (BMC endocrine disorders, 2020)
Background Uric acid (UA) is the end product of purine metabolism, which is thought to be related to many human diseases, such as nephrolithiasis, gout, cardiovascular disease (CVD), type 2 diabetes mellitus, metabolic syndrome. However, the relationship between serum UA (SUA) and 25(OH) D is still unclear in the eastern Chinese population. Methods We did a population-based observational investigation, which included 12,770 residents living in eastern China. Ultimately, data from 9220 subjects were analyzed. Serum 25(OH) D, SUA, fasting plasma glucose (FPG), fasting insulin, HbA1c and other metabolic parameters were tested. Waist circumference (WC), weight and height were also measured. Questionnaires were collected from these subjects for information on smoking and drinking status. Results We enrolled 9220 Chinese adults, including 3681 males (age 55.57 ± 13.23 years) and 5539 females (age 54.31 ± 12.83 years). The levels of SUA were 352.07 ± 79.25 nmol/L and 269.29 ± 64.68 nmol/L in males and females, respectively. The proportion of adults with hyperuricemia (HUA) was 12.26% in the total population. Levels of SUA were positively associated with 25(OH) D, and the incidence of HUA increased 9.4% for every 10 nmol/L increase in 25(OH) D ( P < 0.001). Conclusions SUA was positively associated with 25(OH) D in the eastern Chinese population. Higher levels of serum 25(OH) D may be a potential predictor of HUA.